Análisis De La Nia 500: Procedimientos Para La Obtención De Evidencia En Auditorías Financieras (2025)
This article is aimed at students or trainee auditors who wish to strengthen their knowledge or resolve doubts regarding the application of financial audits. It addresses important topics of ISA 500, focusing on the audit procedures for obtaining evidence, as this is a crosscutting issue that auditors use to support their opinion. The standard discusses two key characteristics: sufficiency, which refers to the quantity, and appropriateness, which refers to the quality of the evidence.